Video‐assisted thoracic surgery and jejunal reconstruction in a case of situs inversus totalis with esophageal cancer. Issue 4 (6th July 2017) - Hosoda, Kei; Yamashita, Keishi; Moriya, Hiromitsu; Nemoto, Mitsuru; Mieno, Hiroaki; Ema, Akira; Washio, Marie; Watanabe, Masahiko
Abstract: A 78‐year‐old man with situs inversus totalis who had a previous history of distal gastrectomy for gastric cancer was referred to our hospital for treatment of esophageal cancer. He was diagnosed as cT2N0M0 and underwent video‐assisted thoracic surgery and open completion gastrectomy with jejunal reconstruction via the ante‐thoracic route. The postoperative period was uneventful except for transient palsy of the right recurrent laryngeal nerve. Based on a preoperative assessment of anatomical abnormality and an intraoperative adaptation to the mirror image of the standard procedure, video‐assisted esophagectomy was considered safe and feasible. It can be recommended for patients with esophageal cancer complicated by situs inversus totalis. This is the first case report of a patient with situs inversus totalis who underwent video‐assisted esophagectomy with jejunal reconstruction. Relevant literature is also discussed and reviewed.